Postnatal Loss of Neuronal and Glial Neurofascins Differentially Affects Node of Ranvier Maintenance and Myelinated Axon Function - Taylor, Anna M.; Saifetiarova, Julia; Bhat, Manzoor A. (Frontiers in Cellular Neuroscience, 2017)
Abstract: Intricate molecular interactions between neurons and glial cells underlie the creation of unique domains that are essential for saltatory conduction of action potentials by myelinated axons. Previously, the cell surface adhesion molecule Neurofascin (Nfasc) has been shown to have a dual-role in the establishment of axonal domains from both the glial and neuronal interface. While the neuron-specific isoform of Neurofascin (NF186) is indispensable for clustering of voltage-gated sodium channels at nodes of Ranvier; the glial-specific isoform of Neurofascin (NF155) is required for myelinating glial cells to organize the paranodal domain. Although many studies have addressed the individual roles of NF155 and NF186 in assembling paranodes and nodes, respectively; critical questions about their roles in the maintenance and long-term health of the myelinated axons remain, which we aimed to address in these studies. Here using spatiotemporal ablation of Neurofascin in neurons alone or together with myelinating glia, we report that loss of NF186 individually from postnatal mice leads to progressive nodal destabilization and axonal degeneration. While individual ablation of paranodal NF155 does not disrupt nodes of Ranvier; loss of NF186 combined with NF155 causes more accelerated nodal destabilization than loss of NF186 alone, providing strong evidence regarding a supporting role for paranodes in nodal maintenance. In both cases of NF186 loss, myelinating axons show ultrastructural changes and degeneration. Our studies reveal that long-term maintenance of nodes and ultimately the health of axons is correlated with the stability of NF186 within the nodal complex and the presence of auxiliary paranodes.